Effects of Climate, Soil, Topography and Disturbance on Liana Prevalence - Mackintosh, Emma J.; Waite, Catherine E.; Putz, Francis E.; Pfeifer, Marion; Chen, Chengrong; Lan, Zhongming; Brennan, Sophie; Marshall, Andrew R. (Ecology and evolution, 2024)
ABSTRACT Lianas (woody vines and climbing monocots) are increasing in abundance in many tropical forests with uncertain consequences for forest functioning and recovery following disturbances. At a global scale, these increases are likely driven by disturbances and climate change. Yet, our understanding of the environmental variables that drive liana prevalence at regional scales is incomplete and geographically biased towards Latin America. To address this gap, we present a comprehensive study evaluating the combined effects of climate, soil, disturbance and topography on liana prevalence in the Australian Wet Tropics. We established 31 20 × 20 m vegetation plots along an elevation gradient in low disturbance (canopy closure ≥ 75%) and high disturbance (canopy closure ≤ 25%) forest stands. In these plots, all tree and liana (defined as all woody dicot vines and climbing monocots, i.e., rattans) stems ≥ 1 cm DBH were measured and environmental data were collected on climate, soil and topography. Generalised linear models were used with multi‐model averaging to quantify the relative effects of the environmental variables on measures of liana prevalence (liana–tree basal area ratio, woody vine basal area and stem density and rattan stem density). Liana prevalence decreased with elevation but increased with disturbance and mean annual precipitation. The increase in the liana–tree ratio with precipitation was more pronounced for highly disturbed sites. Like other tropical regions, disturbance is an important driver of liana prevalence in Australian rainforests and appears to interact with climate to increase liana–tree ratios. The observed increase in liana–tree ratio with precipitation contrasts findings from elsewhere but is confounded by correlated changes in elevation and temperature, which highlights the importance of regional studies. Our findings show that forests with high disturbance and climatic conditions favourable to lianas are where lianas most likely to outcompete trees and impede forest recovery. Lianas (woody vines and climbing monocots) are highly important in tropical forests; however, our understanding of the environmental variables that drive their proliferation at regional scales is incomplete and geographically biased. We address this gap through a study in the Australian Wet Tropics and find that disturbance and climate are important drivers of liana prevalence. This provides further support for the concern that global change may be contributing to increasing lianas relative to trees, with serious consequences for rates of tropical forest recovery and carbon sequestration.